Assessing the mental health impact of China’s housing boom through national and city-level data analysis - Yige Xiao; Xin Liu; Lijie Ren; Shufang Lai (npj Mental Health Research)
Abstract This study examines the net societal impact of housing price fluctuations on mental health during a housing boom. Analyzing data from 31 Chinese provinces between 2008 and 2019, we identify a significant positive relationship between housing price returns and the rate of psychiatric outpatient visits, suggesting that rising house prices decrease mental health. The results remain robust after controlling for local firms’ stock returns. Placebo tests show that mental health impacts are primarily driven by housing price changes in the patients’ local neighborhoods. Moreover, using City-level data from a hospital in Shenzhen (where housing prices showed the sharpest rise between January 2015 and April 2019), we document a two-week lagged effect of housing price surges on mental health Deterioration, which takes slightly longer to manifest than the negative effect of stock market fluctuations. Overall, our findings suggest that housing booms deteriorate mental health and increase the societal burden on healthcare systems.